Buho: The inclusive privacy assistant for the Internet of things (2021)
This project proposes Buho, a novel and open-source privacy assistant for the Internet of Things. Buho is a privacy-enhancing technology whose goal is to help people regain control over their data in IoT contexts. To achieve this, Buho helps users be aware of IoT devices, their risks, and their privacy policies when available. Unlike other existing IoT privacy assistant proposals, Buho is highly customizable to be able to adapt to different types of users with varying privacy perceptions and needs. Additionally, Buho relies on a privacy-centered architecture, it was designed to be inclusive, and it allows users to set their desired IoT detection scheme through which it identifies the user's owned and non-owned IoT devices. Moreover, a usability study was conducted to evaluate users' perceptions on the proposed IoT privacy assistant (e.g., how easy it is to use, how clear the information shown is, and how effective it is providing people with more control over their data). In general, most respondents highlighted that Buho is simple to use, the information about IoT devices shown is clear, and that they liked that it provided them with tips to protect their privacy in IoT contexts. Finally, Buho is a useful tool because it empowers people to take more informed decisions that affect their privacy in IoT scenarios and considers the needs of people living in a developing country, which is important as privacy is a human right and everyone should be informed and capable of protecting it, regardless of their background.